2022
DOI: 10.1111/vsu.13903
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic measurements of the femoral trochlea in dogs with and without medial patellar luxation

Abstract: Objectives: To determine cutoff values in small (SB) and medium/large (MLB) breed dogs with and without medial patellar luxation (MPL) for identifying abnormal femoral trochlea morphology. Study design: Original research.Animals: A total of 80 computed tomographic (CT) scans from client-owned dogs Methods: Four groups of 20 dogs were created: (1) control SB, (2) control MLB, (3) MPL-SB, and (4) MPL-MLB. Two authors measured the femoral trochlear groove angle (FTGA), femoral trochlear angle (FTA), and femoral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
(123 reference statements)
0
0
0
Order By: Relevance
“…luxation exhibited a different femoral trochlear groove angle. Small breeds had a shallower femoral trochlear groove angle than medium/large breeds [30].…”
Section: O N G O Et Al Found That Dogs With Medial Patellarmentioning
confidence: 83%
See 1 more Smart Citation
“…luxation exhibited a different femoral trochlear groove angle. Small breeds had a shallower femoral trochlear groove angle than medium/large breeds [30].…”
Section: O N G O Et Al Found That Dogs With Medial Patellarmentioning
confidence: 83%
“…A standardized approach for precisely measuring the femoral trochlear groove using CT has been developed [30,38,42] The femoral trochlea can be evaluated in 3D…”
Section: Imaging Techniques That Can Be Used To Diagnose Trochlear Dy...mentioning
confidence: 99%
“…In dogs from small breeds, patellar luxation occurs as a consequence of complex morphological musculoskeletal abnormalities affecting the entire pelvic limb, but the pathogenetic role of the shallow trochlear groove (Longo et al, 2023) and medial femoral condyle hypoplasia (Garnoeva, 2021) is thought to be the leading cause. Therefore, tangential radiographs of canine stifles are preferred for satisfactory evaluation of trochlear groove depth and shape.…”
Section: Discussionmentioning
confidence: 99%
“…In canine orthopaedics, ROC analysis has been used to evaluate parameters related to developmental diseases, such as hip dysplasia (Gaspar et al, 2016) and medial elbow coronoid disease (Hersh-Boyle et al, 2021). In dogs with patellar luxation, only the cutoff values of femoral trochlear morphological parameters (Longo et al, 2023) and indices of proximodistal patellar position (Murakami et al, 2023) have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation